Do You Want to Know Me? : (Brands as Local Wealth Identity) - Lazuardi, Sofyan; Ardi Setyawan, Mohammad; Suprihandari, Miya Dewi; Ahmad, Muhammad Ali (Journal of Islamic Economics Perspectives, 2022)
Natural wealth is one of the reasons an area makes it an identity. Natural wealth with distinctive characteristics is one of the regional assets that must be maintained and developed. Its development requires sufficient thought and knowledge for the local community and government. Exploration of natural resources should still be carried out wisely for the sake of the future of natural wealth and the region, including the people. South Kalimantan, especially the Cempaka area, contains natural resources that must be preserved, processed and developed wisely in order to improve the economic conditions of the community and the region itself. Efforts to increase knowledge about natural assets and their ownership as well as products produced by the local community, including brands, are very necessary to be carried out by the government and non-governmental organizations that have attention in this field (Dickinson, P., 2001).